INTERACTIONS BETWEEN PUPILS WITH SEVERE MULTIPLE DISABILITY AND TEACHERS - Kantor, Jiří; Ludíková, Libuše; Hutyrová, Miluše; Svoboda, Pavel (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The paper presents a study (mostly of a quality design) aimed at the teacher-pupil interaction performed at the Institute of Special Education Studies, Palacky University in Olomouc. The data was collected by semi-structured interviews, observation of the educational process and a questionnaire survey. Open, axial and selective coding as well as logic analysis of the responses was used for the data analyses. A synthesis of various data as well as various theoretical backgrounds led to the development of a model for the description of the relationship between the teacher and the pupil with severe mental, physical and communicational disability. The paper includes a description of the categories of this model and their process-based classification into inputs, course and outputs.